Современное состояние рынка систем генерации возобновляемых источников энергии - Башта, А.И.; Смирнов, В.О. (Культура народов Причерноморья, 2013)
Рассмотрены основные экономические аспекты рынка устройств энергосбережения в АР
Крым. Указана роль данных положений в развитии возобновляемых источников энергии.
Ключевые слова: экономика, энергосбережение, экономический эффект, устойчивое развитие,
возобновляемые источники энергии, энергетическая политика Розглянуто основні економічні аспекти ринку енергозбереження в АР Крим. Вказана роль
даних положень в розвитку відновлюваних джерел енергії
Ключові слова: економіка, енергозбереження, економічний ефект, сталий розвиток, поновлювані
джерела енергії, енергетична політика The main economic aspects of energy saving devices market in the Crimea. Indicated the role of these
provisions in the development of renewable energy sources.
The development of photovoltaic power systems and heat is especially important for Ukraine due to favorable
climatic conditions.
The analysis showed a significant cost range of prices. Significant fluctuation in prices depends primarily on the
type and manufacturer generating device, as its price is the main part of the cost of the entire system. When
comparing the prices of various solar and photovoltaic systems on the proposal has been selected types of
additional equipment, so the price of the entire system is characterized almost exclusively on the cost of basic
equipment.
Keywords: economy, energy conservation, economic impact, sustainable development, renewable energy, energy
policy